Clinical Application of a Novel Genetic Risk Score for Ischemic Stroke in Patients With Cardiometabolic Disease. Issue 5 (2nd February 2021) - Marston, Nicholas A.; Patel, Parth N.; Kamanu, Frederick K.; Nordio, Francesco; Melloni, Giorgio M.; Roselli, Carolina; Gurmu, Yared; Weng, Lu-Chen; Bonaca, Marc P.; Giugliano, Robert P.; Scirica, Benjamin M.; O'Donoghue, Michelle L.; et al.
Abstract : Background: Genome-wide association studies have identified single-nucleotide polymorphisms that are associated with an increased risk of stroke. We sought to determine whether a genetic risk score (GRS) could identify subjects at higher risk for ischemic stroke after accounting for traditional clinical risk factors in 5 trials across the spectrum of cardiometabolic disease. Methods: Subjects who had consented for genetic testing and who were of European ancestry from the ENGAGE AF-TIMI 48 (Effective Anticoagulation with Factor Xa Next Generation in Atrial Fibrillation), SOLID-TIMI 52 (Stabilization of Plaques Using Darapladib), SAVOR-TIMI 53 (Saxagliptin Assessment of Vascular Outcomes Recorded in Patients with Diabetes Mellitus), PEGASUS-TIMI 54 (Prevention of Cardiovascular Events in Patients With Prior Heart Attack Using Ticagrelor Compared to Placebo on a Background of Aspirin), and FOURIER (Further Cardiovascular Outcomes Research With PCSK9 Inhibition in Patients With Elevated Risk) trials were included in this analysis. A set of 32 single-nucleotide polymorphisms associated with ischemic stroke was used to calculate a GRS in each patient and identify tertiles of genetic risk. A Cox model was used to calculate hazard ratios for ischemic stroke across genetic risk groups, adjusted for clinical risk factors. Results: In 51 288 subjects across the 5 trials, a total of 960 subjects had an ischemic stroke over a median follow-up period of 2.5 years. After adjusting for clinical risk factors, a higher GRS was strongly and independently associated with increased risk for ischemic stroke ( P trend=0.009). In comparison with individuals in the lowest third of the GRS, individuals in the middle and top tertiles of the GRS had adjusted hazard ratios of 1.15 (95% CI, 0.98–1.36) and 1.24 (95% CI 1.05–1.45) for ischemic stroke, respectively. Stratification into subgroups revealed that the performance of the GRS appeared stronger in the primary prevention cohort with an adjusted hazard ratio for the top versus lowest tertile of 1.27 (95% CI, 1.04–1.53), in comparison with an adjusted hazard ratio of 1.06 (95% CI, 0.81–1.41) in subjects with previous stroke. In an exploratory analysis of patients with atrial fibrillation and CHA2 DS2 -VASc score of 2, high genetic risk conferred a 4-fold higher risk of stroke and an absolute risk equivalent to those with CHA2 DS2 -VASc score of 3. Conclusions: Across a broad spectrum of subjects with cardiometabolic disease, a 32–single-nucleotide polymorphism GRS was a strong, independent predictor of ischemic stroke. In patients with atrial fibrillation but lower CHA2 DS2 -VASc scores, the GRS identified patients with risk comparable to those with higher CHA2 DS2 -VASc scores. Abstract : Supplemental Digital Content is available in the text.